Insights into enzymatic halogenation from computational studies - Senn, Hans M. (Frontiers in Chemistry, 2014)
The halogenases are a group of enzymes that have only come to the fore over the last ten years thanks to the discovery and characterization of several of novel representatives. They have re-vealed the fascinating variety of distinct chemical mechanisms that nature utilizes to activate and introduce halogens into organic substrates. Computational studies using a range of approaches have already elucidated many details of the mechanisms of these enzymes, often in synergistic combination with experiment. This Review summarizes the main insights gained from these stud-ies. It also seeks to identify open questions that are amenable to computational investigations. The studies discussed herein also serve to illustrate some of the limitations of the current computa-tional approaches and the challenges encountered in computational mechanistic enzymology.